Investigate the Moderating Role of Motivation on the Relationship Between People Analytics and Employee Performance - Kaur, Amandeep; Gangwar, Veer P.; Devi, Meenakshi (South Eastern European Journal of Public Health, 2025)
This study investigates the moderating role of motivation in the relationship between People Analytics (PA) and employee performance. Using a structural equation modeling (SEM) approach, data from 300 employees was analyzed to understand the pathways through which PA dimensions—Attraction (ATRCTN), Activation (ACTVTN), and Attraction Intensity (ATRITN)—impact employee performance. The results demonstrate that motivation amplifies the relationship between PA and performance, highlighting its critical moderating role. Practical implications for organizations aiming to enhance employee outcomes through PA are discussed.